Kecemasan dan status gizi berhubungan dengan lama rawat inap pada pasien jantung di RSUD Jenderal Ahmad Yani, Metro, Lampung - Eva Nurlindayanti; Susetyowati Susetyowati; Probosuseno Probosuseno; Retno Pangastuti (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2015)
ABSTRACTBackground: Anxiety is one of the most common psychological problem occured in hospitality patient. The prevalence of anxiety in chronic heart failure patients was 11-45%. Anxiety in heart failure patients could worsening patient’s condition that lead to increased ischemic event, morbidity, negative effects onquality of life, and mortality. Despite anxiety, nutritional status is also one of the most important thing in mantaining patient’s health. Malnutrition has association with increased morbidity, complication, length of stay (LOS), medical therapy, and hospital fees.Objectives: To know the impact of nutritional status and anxiety on LOS in chronic heart failure patients at Jenderal Ahmad Yani General Hospital, Metro, Lampung.Methods: This was an observational quantitative study with cohort prospective design. The research was conducted on July 2014. Subjects were 70 patients who full fi lled the inclusive requirement, patients with anxiety as exposed group and patients without anxiety as non-exposed group. Anxiety was assessedwith Hospital Anxiety and Depression Scale (HADS), while nutritional status was assessed by upper-arm circumference. Data were analyzed with chi-square and logistic regression test.Results: Bivariate test showed that there was significant association between anxiety with LOS (p<0.05). Subjects without anxiety tended to have shorter LOS than that of with anxiety (RR=5.5). There was significant association between nutritional status and LOS (p<0.05). Subjects with normal nutritionalstatus tended to have shorter LOS than that of with undernutrition (RR=2.28). Multivariate test showed that there was an association between anxiety and LOS (p<0.05) with OR=11.22.Conclusions: There was an association between anxiety and LOS. Patients without anxiety had shorter LOS than that of with anxiety. There was association between nutritional status and LOS. Patients with normal nutritional status had shorter LOS than undernutrition patients.KEYWORDS: anxiety, heart failure patients, length of stay, nutritional statusABSTRAKLatar belakang: Kecemasan merupakan salah satu masalah psikologi yang banyak dialami oleh pasien di rumah sakit. Prevalensi kecemasan pada pasien gagal jantung sekitar 11-45%. Kecemasan pada penyakit jantung yang tidak teratasi dapat berakibat pada penurunan kualitas hidup pasien, peningkataniskemik, dan kejadian masuk rumah sakit berulang yang pada akhirnya akan meningkatkan mortalitas. Selain kecemasan, status gizi juga menjadi salah satu faktor penting dalam menunjang kesehatan pasien. Malnutrisi berhubungan dengan peningkatan kesakitan, komplikasi, lama rawat inap, terapi medis, danbiaya perawatan rumah sakit. Tujuan: Mengetahui pengaruh status kecemasan dan status gizi saat masuk terhadap lama rawat inap pada pasien jantung di RSUD Jenderal Ahmad Yani, Metro, Lampung.Metode: Penelitian ini merupakan penelitian observasional kuantitatif dengan rancangan cohort prospective. Penelitian dilakukan pada bulan Juli 2014. Subjek penelitian adalah 70 pasien jantung di RSUD Jenderal Ahmad Yani Metro yang memenuhi kriteria inklusi, dengan kelompok terpapar adalah pasien jantung dengan kecemasan dan pasien jantung tanpa kecemasan sebagai kelompok tidak terpapar. Status kecemasan diukur dengan kuesioner Hospital Anxiety and Depression Scale (HADS), sedangkan status gizi diukur dengan lingkar lengan atas. Data dianalisis dengan uji chi-square dan uji regresi logistik.Hasil: Hasil uji bivariat menunjukkan adanya hubungan bermakna antara status kecemasan dengan lama rawat inap (p<0,05). Subjek tanpa kecemasan cenderung memiliki lama rawat yang lebih pendek (RR=5,5). Ada hubungan yang bermakna antara status gizi dengan lama rawat inap (p<0,05). Subjekdengan status gizi baik cenderung memiliki lama rawat yang lebih pendek daripada subjek dengan status gizi kurang (RR=2,28). Hasil uji multivariat menunjukkan adanya hubungan bermakna antara status kecemasan dengan lama rawat inap (p<0,05) dengan nilai OR=11,22.Kesimpulan: Ada hubungan bermakna antara tingkat kecemasan dengan lama rawat inap. Pasien tanpa kecemasan memiliki lama rawat yang lebih pendek dari pada pasien jantung dengan kecemasan. Ada hubungan bermakna antara status gizi dengan lama rawat inap. Pasien jantung berstatus gizi baik memiliki lama rawat yang lebih pendek daripada pasien jantung berstatus gizi kurang.KATA KUNCI: kecemasan, pasien jantung, lama rawat, status gizi